On a numerical methodology to assess the fatigue life of connecting rods - Xu, Wentao; Le Roux de Bretagne, Olivier; Grasso, Marzio; Harrison, Matthew F.; Carless, Owen; St Leger-Harris, Chris (Sage, 2023)
Although simulation-based fatigue analysis is a standard tool adopted in every sector including automotive industry, the design of engine components in automotive and motorsport applications mostly relies on simplified design approaches supported by time-consuming testing programs. This manuscript proposes a new methodology based on individual engine speed damage estimation and engine speed time history combined with Palmgren-Miner linear damage rule to predict the fatigue state of the connecting rod. The track data, engine multibody simulation (AVL ExciteTM) and engine combustion simulation (AVL BoostTM) are used to generate the initial variable trace that is processed to obtain the block programs. Stress amplitude estimated with finite element analysis (Abaqus) are used to estimate the damage from S-N curve and the cumulative damage is estimated with Palmgren-Miner cumulative damage model. The method proposed is demonstrated using a connecting rod case study and the duty cycle from the race on Sebring international raceway. This work shows the suitability of the approach and the benefit in terms of accuracy in the prediction of the fatigue life.
Keywords: AVL Boost; AVL Excite; connecting rod; internal combustion engine; FEA; variable amplitude fatigue; counting method